Comparative recognition by human IgG antibodies of recombinant proteins representing three asexual erythrocytic stage vaccine candidates of Plasmodium vivax - BARBEDO, Mayara de Brito (2014)
In previous immuno-epidemiological studies of the naturally acquired antibody responses to merozoite surface protein-1 (MSP-1) of Plasmodium vivax, we had evidence that the responses to distinct erythrocytic stage antigens could be differentially regulated. The present study was designed to compare the antibody response to three asexual erythrocytic stage antigens vaccine candidates of P. vivax. Recombinant proteins representing the 19 kDa C-terminal region of MSP-1(PvMSP19), apical membrane antigen n-1 ectodomain (PvAMA-1), and the region II of duffy binding protein (PvDBP-RII) were compared in their ability to bind to IgG antibodies of serum samples collected from 220 individuals from the state of Pará, in the North of Brazil. During patent infection with P. vivax, the frequency of individuals with IgG antibodies to PvMSP119, PvAMA-1, and PvDBP-RII were 95, 72.7, and 44.5% respectively. Although the frequency of responders to PvDBP-RII was lower, this frequency increased in individuals following multiple malarial infections. Individually, the specific antibody levels did not decline significantly nine months after treatment, except to PvMSP119. Our results further confirm a complex regulation of the immune response to distinct blood stage antigens. The reason for that is presently unknown but it may contribute to the high risk of re-infection in individuals living in the endemic areas.